Regulation, Minimum Wage and Informality: Introduction to Symposium. Issue 4 (12th September 2017) - Basu, Kaushik; Dercon, Stefan; Kanbur, Ravi; Svejnar, Jan
Abstract: Are markets in developing and transition economies over‐regulated or under‐regulated? This is a perennial question in the development discourse, but one for which answers appear to come more from preset ideology than from context‐specific analysis and evidence. These issues become even more pressing when the debate turns to the links between regulation, deregulation and inequality. The recent experience of rising inequality in many countries has also brought to the fore predictable policy positions. A key aspect of labor regulation in developing countries, and one becoming more prominent in the era of rising inequality, is the minimum wage. The range of issues around regulation, minimum wage and informality was addressed by papers presented to a conference held in New Delhi on December 17–18, 2014. The conference was co‐sponsored by the World Bank, UK Department for International Development, Cornell University and Columbia University. The organizers of the conference were Kaushik Basu, Stefan Dercon, Ravi Kanbur and Jan Svejnar. A selection of papers from the conference which passed the usual review procedures of the Review of Development Economics, and a further selection of papers from those submitted to the journal, form this symposium.